Analysis of the Value of GSI Scanning Combined with “Double-low” Technology in Head and Neck CTA in Middle-aged and Elderly Individuals - Xiaolong ZHANG; Yingming ZHAO; Guoxiang ZHANG; Fangsheng WEI; Cheng CHEN (CT Lilun yu yingyong yanjiu)
Objective: This study aimed to investigate the value of gemstone spectral imaging (GSI) scanning combined with "double-low" technology in head and neck computed tomography angiography (CTA) in middle-aged and elderly individuals. Materials and Methods: One hundred fifty patients who underwent head and neck CTA from February to December 2023 were retrospectively collected and divided into three groups, comprising 50 patients each, according to different scanning modalities; A, B, and C. Groups A and B underwent conventional spiral scans, with tube voltages of 120 kV and 100 kV, respectively, and tube currents of 300~500 mA were automatically modulated, and the dose and flow rate of the contrast agent were fixed at 55 mL, 4.5 mL/s, saline with the same dose and flow rate for flushing and group C energy spectrum scanning, the tube voltage of the flat scanning group was 80 kV, the tube voltage of the enhancement group was 80~140 kV instantaneous switching, and the tube current was a constant 320 mA in all cases, with a personalized contrast agent injection scheme. The subjective evaluation, objective evaluation, and comparison of contrast use dose were performed on the imaging data of all groups. Results: The mean CT values of head and neck vessels in group B were greater than those in groups A and C, with statistically significant differences. At the aortic arch level, the SNR and CNR parameters in group B were better than those in groups A and C, with statistically significant differences. At the level of the remaining blood vessels, the SNR, CNR, and SD parameters of group C were better than those in groups A and B, excluding the common carotid artery level, with statistically significant differences. The radiation dose in group C was 53.9% and 27.6% lower than that in groups A and B, respectively, and the contrast dose was 27.2% lower. Conclusion: In middle-aged and elderly individuals, head and neck CTA with GSI scanning combined with “double-low” technique can effectively reduce radiation and contrast doses and improve image quality.